Case Report: Complete recovery of a patient with occult septic shock following supranormal vasopressor and inotrope therapy informed by the novel ‘pressure field method’ for managing hemodynamics - Woodford, Stephen F.; Marshall, Ruth C. (Frontiers in Medicine, 2025)
Complete recovery of a patient with occult septic shock and left ventricular ejection fraction of 10% was achieved following management informed by continuous measurement and visualization of the patient’s ‘pressure field’. The ‘pressure field’ visualizes mean perfusion pressure as the product of stroke volume and a beat-to-beat measure of vascular tone, termed systemic elastance. The pressure field guided the titration of inotropes and vasopressors at high doses, including norepinephrine equivalents >2.5 μg/kg/min, to restore the patient’s estimated pre-morbid pressure field values. Urine output was maintained throughout with no ileus. We hypothesize that pressure field management assists in individualizing care for patients with septic shock and improves outcomes.